PERSIAN STUDIES IN INDIA: THE ENDURING LEGACY OF PERSIAN LANGUAGE AND LITERATURE IN INDIAN UNIVERSITIES - Rahman , Md. Mizanur; Ahmed, Rekibuddin (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores the enduring legacy of Persian language and literature in Indian universities, tracing its historical development and contemporary relevance. The study begins with the arrival of Persian in the Indian subcontinent through successive invasions and cultural exchanges, particularly during the Achaemenid, Ghaznavid, Ghurid, and Mughal periods. Persian established itself as the language of administration, literature, and high culture, leaving a profound impact on Indian languages, especially Urdu, as well as on art, architecture, and cultural practices. The paper highlights the significance of Persian in shaping India’s linguistic and literary traditions through figures such as Mirza Ghalib and Allama Iqbal, and historical texts like the Akbarnama and Baburnama. It also examines the institutional role of Indian universities like Aligarh Muslim University, Delhi University, and Jawaharlal Nehru University in preserving and promoting Persian studies. Despite a decline in interest among students due to limited career opportunities and outdated teaching methods, the study emphasizes the potential of digital resources and interdisciplinary approaches to revitalize Persian studies. Through comprehensive academic programs, international collaborations, and cultural initiatives, Persian continues to be a vital part of India’s educational and cultural landscape. The paper argues that with adequate support from academic institutions, cultural organizations, and government policy, the Persian language can maintain its relevance and continue to enrich India’s cultural heritage.